MacOS Ventura - Hart-Davis, Guy (John Wiley & Sons, Inc., 2023)
MacOS Ventura For Dummies is packed with all the information you need on this latest version of macOS. With expert tips, tricks, and troubleshooting ideas, it's the trusted guide for those new to Mac computers and those upgrading their systems. Learn how to organize your files, ensure that your data is secure, work more efficiently, and take advantage of the newest features. Dummies helps you navigate the interface, use helpful shortcuts, and beyond--the easy way. This is the perfect Dummies guide for first-time macOS users, as well as people who are upgrading their systems and need a reference.
Includes index
Keywords: Mac OS; Macintosh (Computer); Operating systems (Computers); Macintosh (Ordinateur); Systèmes d'exploitation (Ordinateurs); operating systems